Integration of Social Values Through Sport - Eko Purnomo; Amung Ma’mun; Nurlan Kusmaedi; Yudy Hendrayana; Nina Jermaina; Akhmad Amirudin; Nessya Fitryona; Dwi Mutia Sari (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Social values are views/rules adopted in human life that are considered good or bad, right or wrong, and beautiful or not beautiful. Social values are used as a way to be able to respect yourself and also other people around you. The purpose of this study is to examine the differences in the results of developing social values through sports activities. The sports activities in question are individual sports (athletics) and team sports (football). The method used in this research is an experiment with a multiple treatment and control design with pretest-posttest. Researchers made an instrument called the social values scale for sport. This study took a sample of students who were carrying out athletic and football learning. There are 4 groups, each group consisting of 30 students. The sample was divided into four groups consisting of 1) intentionally structuring athletics, 2) non-intentionally structuring athletics, 3) intentionally structuring football, and 4) non-intentionally structuring football. In this study, it was found that there was a significant difference in results between the learning groups (athletics and football) intentionally structuring on improving social values or by obtaining a p-value <0.001, which means that there really is a significant difference in the group compared to the learning group (athletics and football) non-intentionally structuring. So, it can be concluded that athletic and football sports activities are a good means to shape social values through intentional structuring. This has an influence on improving outcomes since they not only gain strong talents, but they also ideally develop social values as a provision for our young generation to continue to participate in this globalized competition.